PERANAN PASRAMAN BUDI PAKERTI NAWASENA DALAM PENGUATAN PENDIDIKAN AGAMA HINDU DI DESA BELEGA, BLAHBATUH, GIANYAR - Mahayani, Ni Kadek Eny; Herawan, Kadek Dedy; Karsana, I Nengah (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2025)
One of the organizers of Hindu religious education outside the formal education system that serves to strengthen Hindu religious education is the Pasraman. Pasraman Budi Pakerti Nawasena is one of the non-formal Pasraman in Belega Village, Blahbatuh, Gianyar. Pasraman Budi Pakerti Nawasena serves as a forum dedicated to enhancing Hindu religious education, particularly for children. Pasraman Budi Pakerti Nawasena is one of the solutions for strengthening Hindu religious education for the younger generation of Hindus. The study discusses two main problems: (1) What is the form of Pasraman Budi Pakerti Nawasena in strengthening Hindu religious education? and (2) What is the impact of strengthening Hindu religious education carried out by Pasraman Budi Pakerti Nawasena? The theories used to analyze these problems are Structural Functional Theory and Behaviorism Theory. The subjects of this study were the head of the foundation, Pasraman teachers, and Pasraman students. The research method used was descriptive qualitative. The results of the study showed that (1) Pasraman Budi Pakerti Nawasena is a non-formal educational institution for children in grades 3 to 5 of elementary school. The form of strengthening Hindu religious education implemented at Pasraman Budi Pakerti Nawasena includes strengthening of Acara, strengthening of Susila, and strengthening of Acara. The obstacles faced by Pasraman Budi Pakerti Nawasena are the interests of the students. Efforts made include carrying out varied learning activities that prioritize practice or physical activities. (2) The impact of strengthening Hindu religious education carried out at Pasraman Budi Pakerti Nawasena has an impact on students understanding, ethics, and skills related to the Hindu religious education.